Tourism Blogging Motivations: Why Do Chinese Tourists Create Little "Lonely Planets"?. (April 2016) - Wu, Mao-Ying; Pearce, Philip L.
Chinese tourists, who are increasingly traveling out of Asia independently, need trustworthy and readily available information sources. This study explores the motives of Chinese tourists who have invested considerable time (mostly more than a week) in creating information-rich, influential, and interactive online travel blogs—effectively creating personalized little "Lonely Planets" that serve these growing information needs. This study assesses the demographic characteristics of the "Lonely Planets" creators, the features of their blogging behavior, and the motivations for the involvement. It reveals six motive categories: "positive self-enhancement through online social connection, " "altruism: being helpful to fellow travelers, " "social status issues, " "personal status and achievement, " "self-documentation and sharing, " and "hedonic enjoyment of blogging." Superficially, these motivations seem to be similar with previous Western studies of blogging behavior, but significant contextual and cultural issues exist and are explained. Management implications and future research arising from the current study are provided.